Venous and arterial flow quantification are equally accurate and precise with parallel imaging compressed sensing 4D phase contrast MRI. Issue 6 (21st November 2012) - Tariq, Umar; Hsiao, Albert; Alley, Marcus; Zhang, Tao; Lustig, Michael; Vasanawala, Shreyas S.
Abstract Purpose: To evaluate the precision and accuracy of parallel‐imaging compressed‐sensing 4D phase contrast (PICS‐4DPC) magnetic resonance imaging (MRI) venous flow quantification in children with patients referred for cardiac MRI at our children's hospital. Materials and Methods: With Institutional Review Board (IRB) approval and Health Insurance Portability and Accountability Act (HIPAA) compliance, 22 consecutive patients without shunts underwent 4DPC as part of clinical cardiac MRI examinations. Flow measurements were obtained in the superior and inferior vena cava, ascending and descending aorta, and the pulmonary trunk. Conservation of flow to the upper, lower, and whole body was used as an internal physiologic control. The arterial and venous flow rates at each location were compared with paired t‐tests and F‐tests to assess relative accuracy and precision. Results: Arterial and venous flow measurements were strongly correlated with the upper (ρ = 0.89), lower (ρ = 0.96), and whole body (ρ = 0.97); net aortic and pulmonary trunk flow rates were also tightly correlated (ρ = 0.97). There was no significant difference in the value or precision of arterial and venous flow measurements in upper, lower, or whole body, although there was a trend toward improved precision with lower velocity‐encoding settings. Conclusion: With PICS‐4DPC MRI, the accuracy and precision of venous flow quantification are comparable to that of arterial flow quantification at velocity‐encodings appropriate for arterial vessels. J. Magn. Reson. Imaging 2013;37:1419–1426. © 2012 Wiley Periodicals, Inc.